Morphological alterations and distribution of occludin in rat testes after bilateral vasectomy - ERCAN, FERİHA; ORUN, OYA (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2012)
The aim of study was to investigate the fate and the morphology of the cells which constitute the spermatogenic line, and to determine the distribution of occludin in the testis in adult vasectomized Wistar rats. The rats were divided into two groups: control group (sham-operated) and vasectomized group. One, 3 and 6 months after sham and vasectomy operations, testis samples were examined. The weight of the testes was found to be reduced 3 and 6 months after vasectomy. There was vacuolization in the seminiferous tubules one month after vasectomy. The tubules showed severe atrophy 3 and 6 months after vasectomy. The occludin immunolabeling in the 3- and 6-month groups was weak and diffuse, and the density of the protein was found to be decreased. The increase in the number of apoptotic cells was accompanied by a time-dependent decrease in the number of haploid, diploid and tetraploid cells. This study demonstrated that vasectomy causes degeneration in the seminiferous tubules with alterations in occludin distribution with a decrease in the number of spermatogenic cells. Moreover, these alterations increase in a time-dependent manner. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Apoptosis; Ultrastructure; Occludin; Testis; Vasectomy; Immunohistochemistry; Rat; SPERMATOGENESIS; EPIDIDYMIS; EXPRESSION; JUNCTIONS; SERTOLI